Multisite transformation in Neisseria gonorrhoeae: insights on transformations mechanisms and new genetic modification protocols - Seow, Vui Yin; Tsygelnytska, Olga; Biais, Nicolas (Frontiers in Microbiology, 2023)
Natural transformation, or the uptake of naked DNA from the external milieu by bacteria, holds a unique place in the history of biology. This is both the beginning of the realization of the correct chemical nature of genes and the first technical step to the molecular biology revolution that sees us today able to modify genomes almost at will. Yet the mechanistic understanding of bacterial transformation still presents many blind spots and many bacterial systems lag behind power horse model systems like E. coli in terms of ease of genetic modification. Using Neisseria gonorrhoeae as a model system and using transformation with multiple DNA molecules, we tackle in this paper both some aspects of the mechanistic nature of bacterial transformation and the presentation of new molecular biology techniques for this organism. We show that similarly to what has been demonstrated in other naturally competent bacteria, Neisseria gonorrhoeae can incorporate, at the same time, different DNA molecules modifying DNA at different loci within its genome. In particular, co-transformation of a DNA molecule bearing an antibiotic selection cassette and another non-selected DNA piece can lead to the integration of both molecules in the genome at percentages above 70%. We also show that successive selections with two selection markers at the same genetic locus can drastically reduce the number of genetic markers needed to do multisite genetic modifications in Neisseria gonorrhoeae. Despite public health interest heightened with the recent rise in antibiotic resistance, the causative agent of gonorrhea still doesn’t possess a plethora of molecular techniques. This paper will extend the techniques available to the Neisseria community while providing some insights into the mechanisms behind bacterial transformation in Neisseria gonorrhoeae. We are providing a suite of new techniques to quickly obtain modifications of genes and genomes in the Neisserial naturally competent bacteria.